Effects of Attentional Control on Gait and Inter-Joint Coordination During Dual-Task Walking - Wang, Cenyi; Wang, Guodong; Lu, Aming; Zhao, Ying (Frontiers in Psychology, 2021)
In the process of walking, attentional resources should be flexibly allocated to deal with varying environmental constraints, which is related to attentional control (AC). Dual-task paradigm was used to investigate the effects of AC on gait and inter-joint coordination. Fifty volunteered students participated in this study. The top fifteen participants were assigned to the High Attentional Control group (HAC), and the last fifteen were assigned to the Low Attentional Control group (LAC) according to the reaction time of the Stroop task. Participants in the two groups were asked to perform three tasks randomly: (a) single 2-back task (ST 2-back), (b) single walking task (ST walking), (c) dual-task (DT). Cognitive outcomes and gait spatiotemporal parameters were measured. Continuous relative phase (CRP), derived from phase angles of two adjacent joints, was used to assess inter-joint coordination. Results showed that LAC group exhibited significant effects on the reaction time (RT), correct rate (CR), step width, gait cycle, step time, forefoot contact times, heel-forefoot times, hip-knee mean absolute relative phase (MARP) and deviation phase (DP) in the stance and swing phase (p < .05). Whereas, significant task effects in HAC were only detected in RT and foot progression angle of left foot (p < .05). In addition, both three task conditions, LAC group showed a higher CR in ST, longer heel contact times and longer heel-forefoot times when compared to LAC group (p < .05). HAC group demonstrated significantly smaller (closer to zero) MARP and weaker hip-knee DP values in the swing phase across all gait conditions than LAC (p < .05). Similarly, in the stance phase, HAC group had smaller MARP (closer to zero) values when compared to LAC (p < .05). To conclude, the ability to maintain gait balance and to modulate inter-joint coordination patterns is affected by the level of attentional control in accommodating to gait disturbances in young adults. It was suggested that the ability of attentional control was related with the performances of motor control, which could be used as the theoretical support for the competitive athlete’s selection and fall prevention strategies of falls in older adults.